Self-management of hypertension in a patient with ischemic heart disease: a case report - Koropit, Tessa Ayu; Jamaludin, Thandar Soe Sumaiyah; Hassan, Masmunaa; Nurumal, Mohd. Said; Waliyanti, Ema; Setiawan, Henri (IIUM Press, 2026)
Background: Ischemic heart disease (IHD) remains the leading cause of mortality worldwide, accounting for approximately 16% of global deaths. with hypertension as a major modifiable risk factor. While self-management strategies are widely recommended for blood pressure control, evidence from individual clinical contexts remains limited, particularly in illustrating how patient education supports day-to-day management alongside medical treatment. This case report aims to describe self-management practices and short-term blood pressure outcomes in a patient with uncontrolled hypertension and ischemic heart disease following structured self-management education. Case Presentation: A 65-year-old patient was diagnosed with ischemic heart disease and uncontrolled hypertension. Data was collected through patient interviews, clinical records, and blood pressure monitoring. The self-management intervention included education on lifestyle modification, dietary practices, physical activity, home blood pressure monitoring, and medication adherence. Following the self-management education, the patient demonstrated improved engagement in self-management behaviors, including regular blood pressure monitoring, dietary modification, increased physical activity, and improved medication adherence. A reduction in blood pressure readings was observed over the short follow-up period. However, the patient continued concurrent pharmacological treatment, which may have influenced the observed outcomes. Conclusion: This case report highlights the potential role of self management education in supporting blood pressure control among patients with ischemic heart disease. While improvements were observed the findings should be interpreted cautiously due to confounding